2004
DOI: 10.1108/14769018200400013
|View full text |Cite
|
Sign up to set email alerts
|

Working Partnerships? A Critique of the Process of Multi‐Agency Working in Services to Disabled Children with Complex Health Care Needs

Abstract: Recent government policies in relation to children stress the importance of service integration and partnership working, with particular emphasis on combating social exclusion. With reference to findings from a three‐year empirical study, this article examines some key elements of the process of multi‐agency working in services for disabled children with complex health care needs. It highlights some of the barriers to effective partnerships and lists some pointers for policy and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
0
9
0
Order By: Relevance
“…Although there is wide variability in real‐life implementation models (Halfon et al . 1993; Townsley et al . 2004), our review of the literature indicates that there are three general approaches to the delivery of co‐ordinated care: (i) a system/sector‐based service integration approach reflecting functions and activities focused on integrating services provided by a number of agencies in a geographical area for a particular client group; (ii) an agency‐based service integration approach reflecting functions and activities focused on co‐ordinating the delivery of services across programmes offered by an agency for families in a particular catchment area; and (iii) a client/family‐based service co‐ordination approach reflecting functions and activities focused on assisting specific families to obtain appropriate and needed services from agencies in a geographical area.…”
Section: A Conceptual Framework Of Approaches To the Delivery Of Co‐omentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is wide variability in real‐life implementation models (Halfon et al . 1993; Townsley et al . 2004), our review of the literature indicates that there are three general approaches to the delivery of co‐ordinated care: (i) a system/sector‐based service integration approach reflecting functions and activities focused on integrating services provided by a number of agencies in a geographical area for a particular client group; (ii) an agency‐based service integration approach reflecting functions and activities focused on co‐ordinating the delivery of services across programmes offered by an agency for families in a particular catchment area; and (iii) a client/family‐based service co‐ordination approach reflecting functions and activities focused on assisting specific families to obtain appropriate and needed services from agencies in a geographical area.…”
Section: A Conceptual Framework Of Approaches To the Delivery Of Co‐omentioning
confidence: 99%
“…Service co‐ordinators with systemic roles decide which clients and families will gain access to which services, and make decisions about discharge from services (Austin 1990; Lash & Wertlieb 1993). They may determine the magnitude of the client’s needs, in order to assign clients to different levels of co‐ordination services (Townsley et al . 2004).…”
Section: The System/sector‐based Service Integration Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Townsley and colleagues’ (2004) detailed examination of six different multi‐agency services for disabled children across the UK revealed distinct characteristics relating to multi‐agency working. They built upon Mukherjee and colleagues’ (2000) resource pack which identified three different approaches; autonomous working (separate services with inter‐professional working to achieve specific goals); co‐ordinated working (characterized by joint planning to deliver a co‐ordinated service); and integrated working (holistic, integrated team planning, delivering and funded service) called transdisciplinary working.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that when thinking about collaborative or integrated services it is useful to consider a continuum of integration from organisations working totally independently and coming together for specific tasks to complete merging of services (Percy-Smith, 2005;Townsley et al 2004). There is a considerable literature exploring the factors that help or hinder collaborative working, although it needs to be noted that the evidence in relation to outcomes of integrated work on the lives of children and families is limited (Marsh, 2006 andSloper, 2004).…”
Section: Introductionmentioning
confidence: 99%